Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12888-021-03080-x
|View full text |Cite
|
Sign up to set email alerts
|

Personality inventory for DSM-5 brief form(PID-5-BF) in Chinese students and patients: evaluating the five-factor model and a culturally informed six-factor model

Abstract: Background The Personality Inventory for DSM-5 Brief Form (PID-5-BF) is a 25-item measuring tool evaluating maladaptive personality traits for the diagnosis of personality disorders(PDs). As a promising scale, its impressive psychometric properties have been verified in some countries, however, there have been no studies about the utility of the PID-5-BF in Chinese settings. The current study aimed to explore the maladaptive personality factor model which was culturally adapted to China and to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 54 publications
(21 reference statements)
3
25
0
1
Order By: Relevance
“…For instance, the originally proposed ve-factor model of the personality inventory for DSM-5 brief form (PID-5-BF; 31) was not replicated with Chinese samples, and a six-factor model was proposed in which the Negative Affect domain was divided into two factors. The new factor labeled "Interpersonal Relationships" was consistent with the Big-Six Personality model in China and re ected the humanistic ethic spirit of Chinese culture (32)(33)(34). Similarly, the FFM did not reach a well-t model in some Asian countries (e.g., 35,36,37), and the Openness dimension of the NEO Personality Inventory was poorly replicated in a study with 24 different Asian cultures, including Iran (38).…”
Section: The Current Studymentioning
confidence: 58%
“…For instance, the originally proposed ve-factor model of the personality inventory for DSM-5 brief form (PID-5-BF; 31) was not replicated with Chinese samples, and a six-factor model was proposed in which the Negative Affect domain was divided into two factors. The new factor labeled "Interpersonal Relationships" was consistent with the Big-Six Personality model in China and re ected the humanistic ethic spirit of Chinese culture (32)(33)(34). Similarly, the FFM did not reach a well-t model in some Asian countries (e.g., 35,36,37), and the Openness dimension of the NEO Personality Inventory was poorly replicated in a study with 24 different Asian cultures, including Iran (38).…”
Section: The Current Studymentioning
confidence: 58%
“…Several instruments were used to assess the psychological and psychopathological profile of TTS and ACS patients, including: the Emotion Regulation Questionnaire (ERQ), performed to evaluate individual tendencies to reappraise and to suppress the expression of emotions ( 18 ); the Connor-Davidson Resilience Scale (CD-RISC), used to measure stress coping ability and stress reactions ( 19 ); the DS-14, a measure of negative affectivity and social inhibition, typical features of Type D personality ( 20 ); the PID-5, a useful screening tool for personality disorders ( 21 ); the Mini International Neuropsychiatric Interview (MINI), a short structured diagnostic interview administered to diagnose the most frequent mental disorders ( 22 ) in a revised Italian version according to the current Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria; the Social Readjustment Rating Scale (SRRS), a questionnaire to identify major stressful life events ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Zhang et al (17) found a six-factor model for the structure of the PID-5-BF, which was more applicable than the ve-factor model. In the new six-factor model, the Negative Affect domain was divided into two factors with the new factor, namely "Interpersonal Relationships," which was in line with the Big-Six Personality model in China, re ecting the humanistic ethic spirit of Chinese culture (19)(20)(21). Since the ve-factor model of the PID-5-BF was developed from studies with Western samples, maybe cultural variations underlie different factor structure ndings in the Western and Eastern cultures.…”
Section: Introductionmentioning
confidence: 99%